DNA Methylation in Embryo Development: Epigenetic Impact of ART (Assisted Reproductive Technologies). (21st September 2017) - Canovas, Sebastian; Ross, Pablo J.; Kelsey, Gavin; Coy, Pilar
Abstract : DNA methylation can be considered a component of epigenetic memory with a critical role during embryo development, and which undergoes dramatic reprogramming after fertilization. Though it has been a focus of research for many years, the reprogramming mechanism is still not fully understood. Recent results suggest that absence of maintenance at DNA replication is a major factor, and that there is an unexpected role for TET3‐mediated oxidation of 5mC to 5hmC in guarding against de novo methylation. Base‐resolution and genome‐wide profiling methods are enabling more comprehensive assessments of the extent to which ART might impair DNA methylation reprogramming, and which sequence elements are most vulnerable. Indeed, as we also review here, studies showing the effect of culture media, ovarian stimulation or embryo transfer on the methylation pattern of embryos emphasize the need to face ART‐associated defects and search for strategies to mitigate adverse effects on the health of ART‐derived children. Abstract : DNA methylation, critical for embryo development, suffers significant changes after fertilization, including demethylation, remethylation and TET3‐mediated oxidation of 5 mC to 5 hmC. In addition to infertility and environmental insults, ART (in vitro fertilization, in vitro culture, etc) could impact DNA methylation and ART related consequences in the offspring have been reported.